Shapes: how do you say it? : English, French, Spanish, Italian - Dunham, Meredith (New York : William Morrow & Company, 1987)
Introduces different shapes in illustrations and appropriate descriptive words in Engliash, French, Spanish and Italian.
Keywords: Geometry -- Juvenile literature; Shape; Geometry; Picture dictionary, Polygot